Development and evaluation of a multiplex molecular point-of-care assay for direct identification of Mycobacterium tuberculosis and prioritized non-tuberculous mycobacteria - Yi, Qiao-Lian; Wu, Yun; He, Shuang; Feng, Meng-Li; Liu, Xiao-Yu; Zhou, Xin-Zhu; Gao, Hao-Tian; Zhang, Yu-Fan; Yang, Qi-Wen; Xu, Ying-Chun (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to establish a multiplex molecular point-of-care assay called fastNTM incorporating an ultra-fast sample pre-treatment for direct identification of Mycobacterium tuberculosis complex (MTBC) and 8 non-tuberculous Mycobacteria (NTM) commonly prioritized in clinical settings, and to evaluate its performance in 149 clinical confirmed mycobacterial-positive samples.MethodsThe study was divided into two stages: a pilot study to establish the methodology and a clinical validation study to evaluate its performance. In the pilot study, we established the fastNTM and analyzed its performance regarding limits of detection, reproducibility, specificity and efficiency. The clinical validation study was performed using 149 clinical confirmed mycobacterial-positive samples, with 16S rRNA identification as the reference standard. The complete process, from patient to result, was accomplished within 90 minutes.ResultsOf the 149 positive clinical mycobacterial cultures analyzed, 136 were within the designed targets. Among these 136 cultures, 133 samples were correctly identified by fastNTM, achieving an accuracy rate of 97.79%.ConclusionsThis study demonstrates that fastNTM with its high accuracy rate are capable to rapidly and effectively differentiate between MTBC and the major NTM species.